Identification and Pharmaceutical Characterization of a New Itraconazole Terephthalic Acid Cocrystal - Tajber, Lidia (My University, 2020)
The crystallization of poorly soluble drug molecules with an excipient into new solid phases called cocrystals has gained a considerable popularity in the pharmaceutical field. In this work, the cocrystal approach was explored for a very poorly water soluble antifungal active, itraconazole (ITR), which was, for the first time, successfully converted into this multicomponent solid using an aromatic coformer, terephthalic acid (TER). The new cocrystal was characterized in terms of its solid-state and structural properties, and a panel of pharmaceutical tests including wettability and dissolution were performed. Evidence of the cocrystal formation was obtained from liquid-assisted grinding, but not neat grinding. An efficient method of the ITR–TER cocrystal formation was ball milling. The stoichiometry of the ITR–TER phase was 2:1 and the structure was stabilized by H-bonds. When comparing ITR–TER with other cocrystals, the intrinsic dissolution rates and powder dissolution profiles correlated with the aqueous solubility of the coformers. The rank order of the dissolution rates of the active pharmaceutical ingredient (API) from the cocrystals was ITR–oxalic acid > ITR–succinic acid > ITR–TER. Additionally, the ITR–TER cocrystal was stable in aqueous conditions and did not transform to the parent drug. In summary, this work presents another cocrystal of ITR that might be of use in pharmaceutical formulations. View Full-Text
PUBLISHED
Keywords: Itraconazole; Terephthalic acid; Cocrystal; Crystal structure; Mechanochemistry; Solid-state; Thermal analysis; Wettability; Dissolution; Immunology, Inflammation & Infection; Nanoscience & Materials; DISSOLUTION; ITRACONAZOLE; Pharmaceutical co-crystals; Thermal Analysis; mechanochemistry